Optimizing the School Literacy Movement Program thru the Use of Smart Box Media to Improve Elementary School Students' Literacy Skills - Dianita Ayu Permata; Siswanto, M. Bambang Edi (Global Action and Education for Society, 2025)
This study aims to optimize the implementation of the School Literacy Movement (GLS) through the use of a Smart Box Pancasila to improve the literacy skills of Grade I students at SDN Karangmojo 2. The research was conducted based on the low level of early literacy skills and the limited availability of attractive learning media that align with the developmental characteristics of young learners. This study employed a two-cycle Classroom Action Research (CAR) design with 16 students as research subjects. Data were collected through literacy tests, observation sheets, and documentation during learning activities. The findings indicate that the Smart Box which consists of colorful interactive panels, illustrated cards, Pancasila value pockets, and question panels significantly enhances students’ engagement, interest, and reading abilities. Improvements were evident in students’ ability to recognize letters, read simple words, understand pictures, and read short sentences. Initially, only a small number of students were able to read two-syllable words and interpret visual information; however, by the end of Cycle II, 100% of students could consistently recognize letters, 93.7% were able to read simple words, and 87.5% were able to read short sentences and explain the meaning of the text independently. The study concludes that the Smart Box is an effective literacy medium, as it provides concrete, multisensory, and interactive learning experiences suited to the cognitive development of lower-grade elementary students. This medium is recommended as an alternative GLS support tool to strengthen early literacy learning in primary schools.